A systematic review of interventions to reduce HIV-related stigma among primary and secondary school teachers. Issue 1 (2nd January 2022) - Martin, Roxanne; Ashimosi, Celestine; Nyandiko, Winstone; Chory, Ashley; Aluoch, Josephine; Scanlon, Michael; Vreeman, Rachel
ABSTRACT: HIV/AIDS-related stigma (HIV stigma) affects every aspect of adolescents' HIV management. Adolescents living with HIV (ALWH) are particularly vulnerable in schools where they have described experiencing HIV stigma. Teachers play a significant role in their students' lives. Stigmatizing attitudes or behaviors by teachers not only impact ALWH directly, but may influence the attitudes and behaviors of their peers. There is a dearth of literature exploring interventions to address HIV stigma in school-based settings. The objective of this review is to examine interventions to reduce HIV stigma among teachers globally. To conduct this systematic review, we used the PRISMA guidelines. Two articles met the inclusion criteria. Both eligible studies aimed to reduce HIV stigma among teachers or teachers in training through teacher training interventions in sub-Saharan Africa. The interventions included an interactive CD-ROM, a 2-day workshop, and peer facilitated workshops. Both studies demonstrated a significant decrease in HIV stigma in at least one study measure. Findings from this review are inconclusive. There is evidence to suggest that interventions can successfully decrease HIV stigma among teachers, but it is very limited. More research is needed in order to develop, implement, and evaluate stigma reducing interventions in the classroom.